“HOMILI BERBASIS KEBUTUHAN ANAK: PENGGUNAAN PRAKTIS UNTUK MEMPERKENALKAN FIRMAN TUHAN KEPADA ANAK SEBAGAI TIANG GEREJA - Marpaung, Andre Fernando; Adipati, Yustus; Monika Limbong, Erlin Agnes (Sekolah Tinggi Teologi Berea, Salatiga, 2025)
Abstract:Sunday School is an important place for children to know and understand God's word. Understanding God's Word in Mingu School children is very important because it is the basis of children's faith development. In the discussion of this journal that uses library research methods found that in an effort to convey God's Word to children, the need for Sunday School teachers is very prominent. So Sunday School teachers must also be more creative and have a way of conveying God's word to children. From understanding children's needs and challenges in teaching children continued how homilies can utilize their role to be able to dominate to teach children. The principles of homilies are applied as children's, and varied and informative techniques are widely discussed. This journal provides an understanding of the importance of teaching Sunday School in the formation of children's faith in God's Word to shape the faith of Sunday School children from an early age and as a basis for knowledge of the Bible for faith growth.